Utilization of Electronic Community Library as A Localhost-Based Digital Library in Optimizing Learning Resources - Muhamad Ridwan Sudaryat; Muhammad Fajar Yusuf Firdaus; Adzkia Amatullah Salsabila; Siti Romlah; M. Mardiatunnisa; Wina Nurhayati Praja (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to provide alternative solutions in procuring media sources for teaching materials for students who are constrained by the internet network, especially in the implementation of distance learning during the Corona. Utilization of learning resources with the Electronic network. The method in this study is presented in a descriptive form. The method is in the form of analyzing the problem in the community and identifying potential, including program design, socialization, field observation methods carried out to determine the location of local network installations, program training, and assistance in the implementation of offline digital library systems. The results of alternative solutions resulting from this mentoring process include learning media sources that can be accessed without internet quotas, making them more effective and efficient. Students’ interest in learning is increasing because they utilize the Electronic Community Library. Teachers use more varied sources of teaching materials. The use of the Electronic Community Library can provide a significant influence on the teaching and learning process. The advantages of the Electronic Community are that it is easy to access, has a variety of features, has an attractive appearance, and the maintenance of the device is quite efficient. The Electronic Community Library is a real solution in the world of education, especially for areas that have limitations in accessing the internet network. The Electronic Community Library is not only beneficial for students, but also for teachers, parents, and the community, especially in the development of digital literacy.